Novel aspects in the regulation of the leukocyte adhesion cascade - Chavakis, Emmanouil; Choi, Eun Young; Chavakis, Triantafyllos (Thrombosis and Haemostasis, 2009)
Leukocyte recruitment plays a major role in the immune response to infectious pathogens and during inflammatory and autoimmune disorders. The process of leukocyte extravasation from the blood into the inflamed tissue requires a complex cascade of adhesive events between the leukocytes and the endothelium including leukocyte rolling, adhesion and transendothelial migration. Leukocyte-endothelial interactions are mediated by tightly regulated binding interactions between adhesion receptors on both cells. In this regard, leukocyte adhesion onto the endothelium is governed by leukocyte integrins and their endothelial counter-receptors of the immunoglobulin superfamily. The present review will focus on novel aspects with respect to the modulation of the leukocyte adhesion cascade.
Keywords: Adhesion receptors; cell-cell interactions; endothelial cells; inflammation; integrins